Efficacy and safety of ceftazidime-avibactam in the treatment of complicated intra-abdominal infections (CIAIs) and complicated urinary tract infections (CUTIs): A meta-analysis of randomized controlled trials - Zhang,Yue (2018)
Summary Objective: The aim of this study was to assess the efficacy and safety of ceftazidime-avibactam in the treatment of complicated intra-abdominal infections (CIAIs) and complicated urinary tract infections (CUTIs) with meta-analysis method. Method: We included six randomized clinical trials identified from Medline, Embase, Cochrane Library, “ISRCTN Register” and “ClinicalTrials.gov” which compared ceftazidime-avibactam with comparison group. The meta-analysis was performed using Review Manager software version 5.3. Results: Ceftazidime-avibactam versus active comparisons demonstrated a statistically significant higher rate of microbiological response success on microbiological evaluable populations at the test-of-cure visit (95CI 1.10-2.38, p=0.02) and late-follow-up visit (95CI 1.09-2.23, p=0.02) for the treatment of CUTIs. Ceftazidime-avibactam versus active comparisons demonstrated a statistically significant higher rate of microbiological response success on EME populations at the test-of-cure visit (95CI 1.08-4.27, p=0.03) and late-follow-up visit (OR=1.75, 95CI 1.33-2.29, p<0.0001) for the treatment of CUTIs. Similar results were obtained at the late-follow-up visit (OR = 1.58, 95CI 1.26-1.97, p<0.0001) on microbiologically modified intent-to-treat (mMITT) populations for the treatment of CUTIs. We can find better eradication rates for E. coli and Klebsiella pneumoniae based on mMITT populations. In terms of AEs, SAEs and mortality, ceftazidime-avibactam had a safety and tolerability profile broadly similar to the comparison group. Conclusion: This meta-analysis provides evidence of the efficacy of ceftazidime-avibactam as a potential alternative for the treatment of patients with CUTIs, and CIAIs.